Immune response and cytokine pathways in psoriatic arthritis: A systematic review - Gamze Dilek,; Mehtap Kalcik Unan,; Kemal Nas, (Archives of Rheumatology, 2025)
Objectives: This review aims to focus on the role of innate and adaptive immune system cells and their molecular signaling pathways in the pathophysiology of clinical phenotypes of psoriatic arthritis (PsA). Materials and methods: A systematic literature search was conducted in the PubMed database using the key words “psoriasis,” “psoriatic arthritis,” “pathogenesis,” “adaptive immune system,” “pathophysiology,” “bone and cartilage damage,” and “cytokine pathways.” Results: Clinical studies and in vitro studies on adaptive and innate immune system cells and mediators that cause activation of these cells in the pathogenesis of PsA were examined. The role of cytokine pathways affecting the pathogenesis of PsA on the most common clinical phenotypes of the disease were explained in detail. Conclusion: In this article, we reviewed the cytokine pathways that may contribute to the immunological pathogenesis of psoriatic arthritis. We believe that this review will contribute to a better understanding of the pathogenesis of the clinical phenotypes of the disease and to disease management.